(untitled) (Journal of Mathematical Study, 2018)
In 2007, T. Hosokawa and S. Ohno gave the sufficient and necessary conditions of the boundedness and compactness of differences of composition operators on the Bloch space. On this base, this paper will generalize these conditions of the boundedness and compactness of differences of composition operators on the Bloch type space.